1981
DOI: 10.1126/science.7268445
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stress-Induced Analgesia and Activation of the Opiate System

Abstract: Exposure of rats to a series of inescapable shocks produced in sequence both an early naltrexone-insensitive and a late naltrexone-reversible analgesic reaction. Activation of the opiate system was necessary and sufficient to produce an analgesic reaction 24 hours later on exposure to a small amount of shock. The amount of inescapable shock which induced naltrexone-reversible analgesia also produced hyperreactivity to morphine 24 hours later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
145
4

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(161 citation statements)
references
References 15 publications
(2 reference statements)
12
145
4
Order By: Relevance
“…This response may follow a period of active but unsuccessful engagement with a source of stress, and is characterized by quiescence, hypotension, decreased responsiveness to the environment, and prolonged opioid-mediated analgesia (Grau et al, 1981;Keay and Bandler, 2001;Ribeiro et al, 2005). In the present study high levels of discouragement apparently evoked opioid release which, in turn, 'capped' painful sensations during the final cold pressor test.…”
Section: Discussionmentioning
confidence: 55%
“…This response may follow a period of active but unsuccessful engagement with a source of stress, and is characterized by quiescence, hypotension, decreased responsiveness to the environment, and prolonged opioid-mediated analgesia (Grau et al, 1981;Keay and Bandler, 2001;Ribeiro et al, 2005). In the present study high levels of discouragement apparently evoked opioid release which, in turn, 'capped' painful sensations during the final cold pressor test.…”
Section: Discussionmentioning
confidence: 55%
“…The effect of ADX is a long-lasting phenomenon persisting for a period as long as 7 or even 14 days. A similar long-term effect was obser ved also for stress-induced analgesia (15,20,21]. MacLennan et al [21] suggested that corticosterone is of critical im portance in the development of the long-term opioid form of stress-induced analgesia.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, some kinds of stimulus-pro duced analgesia depend on the integrity of the adreno-hypophyseal axis [Watkins and Mayer, 1982] and stressful stimuli have been found to elicit long-lasting analgesic effects [Grau et al, 1981], Since amphetamine in duces release of both pro-opiomelanocortine derivatives from adenohypophysis and of glucocorticoids from adrenal cortex, [Brown et al, 1978;Knych andEisenberg, 1980;Co hen et al. 1981], we also tested the possibility that cathinone is a pharmacological equiva lent of stress in eliciting analgesia.…”
Section: Introductionmentioning
confidence: 99%